PELATIHAN EVAKUASI DAN TRANSPORTASI PADA DRIVER AMBULANS LAZIZMU BANYUMAS - Endiyono, Endiyono; Adhi, M. Hanif Prasetya (Universitas Muhammadiyah Tangerang, 2021)
Accidents or unwanted events can happen anywhere and anytime. This incident can be a small incident or a disaster involving a large number of sufferers. Those who attempt to provide this help have varying degrees of knowledge ranging from no knowledge to those who may have been trained. There is a golden time between assistance in the field until the victim can get help by medical personnel at a health facility, so this response time must be used properly so that the victim will survive. The speed of evacuation of victims of traffic accidents is one of the important goals in emergency assistance. In a dangerous situation, a rescuer may need to move the patient immediately. In a dangerous situation, it is very important for rescuers to take appropriate, fast and alert action. Ambulance is a specially designed medical transportation that is different from other modes of transportation. The emergency ambulance is designed to be able to handle emergency patients, provide first aid and perform intensive care during the trip to the referral hospital. This activity was carried out by conducting evacuation and transportation training for the Lazizmu Banyumas ambulance driver and the Banyumas ambulance community which was attended by 38 drivers. This training uses lectures, demonstrations and red-emonstration methods on how to evacuate and transport patients. The result of this training is an increase in driver skills in evacuating and transporting patients in accordance with standard operating procedures (SOPs). The impact of this service is to increase the confidence of ambulance drivers in providing first aid in prehospital events.